OPTIMIZED SOLID LIPID NANOPARTICLES FOR ENHANCED ORAL BIOAVAILABILITY AND OSTEOGENIC EFFECT OF IPRIFLAVONE: FORMULATION, CHARACTERIZATION, AND IN VITRO EVALUATION - V., ANOOP NARAYANAN; JOHN, ANISH; P. R., SUMUKH; PRIYA, SNEH; RAVIRAJ, CHAITHRA; ASHTEKAR, HARSHA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to enhance the oral bioavailability of Ipriflavone (IP) and evaluate its osteogenic effect on human osteosarcoma cells (MG-63) by developing Ipriflavone-loaded Solid Lipid Nanoparticles (IP-SLN). Methods: IP-SLNs were prepared using a modified solvent evaporation method with probe sonication. Formulation optimization employed Central Composite Design (CCD) with independent variables, including lipid amount, surfactant concentration, and sonication time. Characterization was performed using Transmission Electron Microscopy (TEM). In vitro drug release and ex vivo permeation studies were conducted to assess drug release kinetics and bioavailability. Cytotoxicity, Alkaline Phosphatase (ALP) activity, and calcium deposition studies on MG-63 cells evaluated osteogenic effects. Results: TEM images showed round particles with an average diameter of 43.24±3 nm, a zeta potential of-9.53 mV, and a drug entrapment efficiency of 76.53±1.84%. In vitro drug release from IP-SLN was 79.02% compared to 14.21% from IP after 48 h, following the Korsmeyer-Peppas model and first-order kinetics. Ex vivo permeation of IP-SLN was approximately 2-fold higher than IP dispersion. Cytotoxicity studies revealed no toxicity on MG-63 cells. ALP activity and calcium deposition studies indicated that IP-SLN stimulated osteoblast differentiation, increasing alkaline phosphatase activity and mineralization. Pharmacokinetic studies demonstrated that IP-SLN increased the relative bioavailability by 515% compared to ipriflavone. Conclusion: IP-SLN formulations significantly improved the oral bioavailability and osteogenic effects of ipriflavone on MG-63 cells, suggesting potential for novel therapeutic applications in osteoporosis treatment.